Integrating The Network Pharmacology and Molecular Docking to Uncover The Potential Mechanism Of Rutin In Fighting Diabetes Mellitus - Putri, Stella Anatasya Putri; Maharani, Andi Rani Gustia; Luthfiana, Dewi; Nweze, Leonard Chinecherem; Setiawansyah, Arif; Susanti, Gita; Doloking, Haeria (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2024)
Introduction: Rutin is a flavonol glycoside that is known to have blood sugar reducing activity. However, its molecular mechanism in reducing blood sugar level remains unclear. This study was employed to elucidate the pharmacological mechanism of rutin as antidiabetic agent. Methods: Potential target of rutin was screened in relevant databases to construct a compound-target network. Network pharmacology was utilized to identify targets associated with disease, gene ontology and KEGG pathways and confirmed its potential binding affinity using Autodock 4.2 assisted by ADT interface. Result: The result highlighted mTor, PIK3R1, and NFKB1R as a potential target of Rutin through network pharmacology. This target involved in the insulin signaling pathways, insulin resistance, type 2 diabetes mellitus, B receptor signaling pathways, AGE-RAGE signaling pathway in diabetic complications and pancreatic cancer. All docking protocols were valid with RMSD value for TNF-a, NF-KB, PI3K were 0.72 Å, 0.67 Å, ​​and 0.54 Å, respectively. The molecular docking has confirmed the potential mechanism of rutin as antidiabetic agent by stably bound with these proteins with estimated free binding energy values of -8.54 kcal/mol (NF-KB), -8.01 kcal/mol (PI3K), and -6.22 kcal/mol (TNF-a). Conclusion: The study has given insight into the molecular mechanism of rutin in the management of DM by stably bound with NF-KB, TNF-a, and PI3K. However, further laboratory experimental research is needed, particularly in vitro and in vivo assay